Impact of bronchoalveolar lavage from influenza A virus diseased pigs on neutrophil functions and growth of co-infecting pathogenic bacteria - Simon Lassnig; Simon Lassnig; Isabel Hennig-Pauka; Isabel Hennig-Pauka; Marta C. Bonilla; Marta C. Bonilla; Matthias Mörgelin; Rabea Imker; Rabea Imker; Maren von Köckritz-Blickwede; Maren von Köckritz-Blickwede; Nicole de Buhr; et al. (Frontiers in Immunology, 2024)
IntroductionInfluenza A viruses (IAVs) infect the respiratory tract of mainly humans, poultry, and pigs. Co-infections with pathogenic lung bacteria are a common event and contribute to the severity of disease progression. Neutrophils are a major cell type of the innate immune system and are rapidly recruited to the site of infection. They have several effector functions to fight invading pathogens such as the secretion of reactive oxygen species (ROS) or the release of neutrophil extracellular traps (NETs). NETs are known to promote the growth of Pasteurellaceae bacteria, especially if degraded by nucleases.MethodsIn this study, bronchoalveolar lavage fluid (BALF) from 45 field-infected pigs was analyzed for 1) NET markers, 2) influence on growth of lung bacteria, and 3) impact on neutrophil functions. BALF samples from 21 IAV-positive pigs and 24 lung diseased but IAV-negative pigs were compared.ResultsHere, we show that neutrophils in the lungs of IAV-positive pigs release vesicular NETs. Several NET markers were increased in the BALF of IAV-positive pigs compared with the BALF from IAV-negative pigs. The amount of NET markers positively correlated with the viral load of the IAV infection. Interestingly, the BALF of IAV-positive pigs enhanced the growth of bacteria belonging to the family of Pasteurellaceae as potential coinfecting bacteria. These effects were weaker with the BALF derived from IAV-negative pigs with other lung infections. The intensity of oxidative burst in neutrophils was significantly decreased by BALF from IAVpositive pigs, indicating impaired antimicrobial activity of neutrophils. Finally, the lung milieu reflected by IAV-positive BALF does not enable neutrophils to kill Actinobacillus pleuropneumoniae but rather enhances its growth.DiscussionIn summary, our data show that an IAV infection is affecting neutrophil functions, in particular the release of NETs and ROS. Furthermore, IAV infection seems to provide growth-enhancing factors for especially coinfecting Pasteurellaceae and reduces the killing efficiency of neutrophils.